Responses of Selected Indonesian Rice Varieties under Excess Iron Condition in Media Culture at Seedling Stage - Nugraha, Yudhistira; Ardie, Sintho Wahyuning; Rumanti, Indrastuti A.; Suwarno, Suwarno; Ghulammahdi, Munif; Aswidinnoor, Hajrial (Jurnal Penelitian Pertanian Tanaman Pangan, 2016)
Iron toxicity could limit rice productivity on irrigated lowland acid and swampy soil. The use of iron toxicity tolerant rice is an alternative strategy to improve rice productivity in these areas. We studied the phenotypic variation of twenty-four rice genotypes and characterized the fate of Fe2+ along its path between the roots and shoot of rice plant. Twenty-four rice genotypes form different agro-ecosystem were grown under agar nutrient solution conditions with 400 mg. L-1 iron stress and under normal condition. We found variation in the biomass accumulation of rice seedling during stress of iron namely, high accumulated biomass tolerant type and low accumulate biomass tolerant type. The relative biomass weight was highly correlated with the leaf bronzing scores (LBS) under excess iron. Based on these categorizations, we chose six genotypes to observe the present of Fe in root and shoot using invivo-staining 2,2 bypiridine. The result indicated that some genotypes were able to develop root and shoot aerenchym during iron stress. This was related to the development on root iron plaque and the iron content of the shoot of the rice seedling. In this present study, rice genotypes could be classified as the includer tolerant type (Inpara 2) and some others were the excluder tolerant type (Mahsuri, Pokkali and Siam Saba). This information on tolerance strategies is important for rice breeder to develop physiological-based breeding program of iron-toxicity tolerant in rice.